Global paradox : the bigger the world economy, the more powerful its smallest players - Naisbitt, John (Nicholas Brealey Pub. LondonGB, 1995)
Shows how the small is powerful revolution is already in action, and it offers an exciting vision of a new global environment and of the awesome mix of opportunities and challenges which it represents.